Participatory Leadership for Smart Village Development - Annisa, Nur; Ikbal, Muhammad; Sundari, Sundari (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This study aims to analyze the role of participatory leadership in supporting Smart Village development in Bulo Village, Sidenreng Rappang Regency. Using a descriptive quantitative approach, this study describes the relationship between indicators of communication, cooperation, subordinate involvement, and decision-making and the success of Smart Village development. Data were collected through observation, in-depth interviews, and questionnaires given to 100 respondents, then analyzed using the SPSS 26 application for Windows. The results showed that respondents rated participatory leadership in Bulo Village very well, with an average percentage of 86 percent on all four indicators studied. These findings suggest that the inclusive and participatory leadership approach has created an enabling environment for active community participation, an important foundation for implementing the Smart Village concept. However, challenges remain, particularly in decision-making and subordinate involvement, that require further improvement. The implications of this study emphasize the importance of effective communication, cooperation, and subordinate involvement in participatory leadership models, particularly in the context of technology-based development such as Desa Cerdas. From a practical perspective, this research offers concrete recommendations for village governments and local leaders to develop and implement the Desa Cerdas concept more effectively. The limitations of this study include the limited scope of one village and a quantitative approach that lacks depth in uncovering social and cultural dynamics. Further research using qualitative approaches or case studies in various villages is needed to gain more comprehensive insights.